Impact of sludge blending on the air pollutant control devices in a coal-fired power plant - Weiqun WANG; Zhijun HUANG; Enxian ZHANG; Yuanqiang DUAN; Lunbo DUAN (Meitan xuebao)
Using coal-fired power plants for co-firing can achieve efficient consumption of sludge, and the existing Air Pollutant Control Devices (APCDs) in coal-fired power plants can effectively control the pollutants generated by sludge combustion. However, the experience of power plants also indicates that sludge co-firing may have adverse effects on the stable operation of APCDs. This study conducted sludge co-firing experiments and field tests on a 660 MWe power unit, investigated the impact mechanism of sludge co-firing on trace element distribution, ash characteristics, and evaluated the potential influence of sludge blending on SCR de-NOx, Electrostatic Precipitator (ESP) and wet Flue Gas Desulfurization (FGD) systems. The mixture of municipal and printing/dyeing sludge used in the experiment contained higher concentrations of Ni, Cu, Zn and Mn elements, but the distribution of heavy metal elements in the system did not change at a 5% sludge blending ratio. Except for Hg, most of the heavy metal elements were still distributed in the particle phase, with only a small amount of Pb, Cr and Ni elements appear in desulfurization gypsum. Cl element content in the sludge used in the experiment is much higher than that of the raw coal. HCl and Cl2 concentrations in the flue gas were sampled and tested at the entrance of the SCR reactor using EPA Method 26A. The results showed that more than 75% of Cl element in the fuel was released into the flue gas in the form of HCl during the combustion process, causing a high concentration of Cl− ions in the desulfurization slurry. The generation of PM1 to PM10 ultrafine particles after co-firing is lower than that under non co-firing conditions, and the higher concentrations of Fe2O3 and P2O5 in the sludge ash reduced its resistivity, which is beneficial for improving the efficiency of ESP after co-firing. More fine particles enter the desulfurization slurry after co-firing, making it difficult to dehydrate the gypsum. And the increase in Cl− concentration in the slurry further leads to an increase in gypsum moisture content.